Depressive-like psychoemotional state versus acute stresses enhances Lewis lung carcinoma metastasis in C57BL/6J mice - Amikishieva, A.V.; Ilnitskaya, S.I.; Nikolin, V.P.; Popova, N.A.; Kaledin, V.I. (Experimental Oncology, 2011)
Aim: The effect of a depression-like status formed by chronic stress on the development of Lewis lung carcinoma metastases in C57Bl/6J mice was investigated. Two types of acute stress (restraint and social stress) were used for comparison. Methods: The depression-like status was induced by eight-week exposure to repeated but unpredictable stressors (chronic mild stress model) and was assessed in the forced swim test. Tumor cells were inoculated an hour after the onset of social stressor or immediately after physical or chronic stressor impacts. The number of metastases was counted 17 days after the inoculation. Results: Chronic mild stress provokes the development of a depression-like state in mice and causes a twofold increase in the number of metastases in the lungs, while both types of acute stress have no such effects. Conclusion: Depressive-like psychoemotional state of animals enhances the metastasis of Lewis lung carcinoma.